The impact of agricultural product branding on farmers’ income inequality: evidence from China - Zheng, Jialong; Li, Guangsi (Frontiers in Sustainable Food Systems, 2024)
Introduction: Income inequality is related to farmers' welfare, access and satisfaction. Addressing income inequality among farmers is particularly urgent as it is growing. So, as an important symbol of the development of the agricultural industry, what is the impact of agricultural product branding on farmers' income inequality? Methods: To answer this question, this paper uses panel data from 1986 counties in China from 2000 to 2021 and employs the Recentered Influence Function (RIF) method to explore the impact of agricultural product branding (APB) on farmers' income inequality and its mechanism of action. Results and discussion: The results of the study show that while the APB boosted farmers' incomes by an average of 1.6%, they exacerbated farmers' income inequality by an average of 0.4% (using the Gini coefficient as an example). Mechanistic analysis shows that the APB exacerbates farmers' income inequality by widening the gap between counties in terms of the level of adoption of agricultural technology and agricultural labor productivity. Heterogeneity analysis reveals that, compared to non-agricultural provinces, the APB in agricultural provinces reduces interregional farmers’ income inequality. Furthermore, the APB in the grain category mitigates this inequality, whereas the APB in the cash crop and aquatic product categories exacerbates it. The APB in the livestock category, however, has no significant effect on interregional farmers’ income inequality. Considering these findings, the government should regularly assess the impact of agricultural branding policies on income inequality among farmers and adjust policies in a timely manner to ensure their effectiveness and fairness.